2005
DOI: 10.1161/circulationaha.104.496224
|View full text |Cite
|
Sign up to set email alerts
|

Giant Aneurysm of the Right Coronary Artery Compressing the Right Heart

Abstract: A 45-year-old woman with a 5-year history of treated essential hypertension presented with a 2-month history of exertional dyspnea and a 2-week history of intermittent palpitations. Two weeks earlier, she presented to the emergency department of another hospital with palpitations, but these had terminated on arrival. She was told her ECG displayed "low voltages." During the next 2 weeks, she became increasingly dyspneic, feeling short of breath most of the time. She had a sensation of fullness in the chest, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…It is suggested that CAAs can cause ischemia and myocardial infarction by leading to slow coronary flow, turbulent flow, in-situ thrombosis, spontaneous dissection, and microembolus (6,11,13,14). The most important predictor of myocardial infarction is the diameter of the aneurysm (15,16). In the present case, the giant aneurysm led to non-ST elevation myocardial infarction.…”
Section: Case Reportmentioning
confidence: 52%
“…It is suggested that CAAs can cause ischemia and myocardial infarction by leading to slow coronary flow, turbulent flow, in-situ thrombosis, spontaneous dissection, and microembolus (6,11,13,14). The most important predictor of myocardial infarction is the diameter of the aneurysm (15,16). In the present case, the giant aneurysm led to non-ST elevation myocardial infarction.…”
Section: Case Reportmentioning
confidence: 52%
“…Kawasaki’s disease) by origin [3]. If not identified early or managed appropriately, complications such as thrombosis of the vessel with resultant myocardial ischemia, aneurysmal rupture with acute pericardial tamponade, or direct compressive effects from the mass lesion resembling an obstructive cardiomyopathy can occur [5,6]. …”
Section: Resultsmentioning
confidence: 99%
“…Giant coronary artery aneurysm is a rare entity that has been previously reported. 1 Association with other aneurysmal diseases such as abdominal aneurysm has also been reported, but remains a very rare phenomenon. 2,3 Underlying causes associated with dilatations of blood vessels systemically include degenerative processes (atherosclerosis being a major cause), infections (such as syphilis), inflammation (such as Kawasaki Disease and Behcet's syndrome 2 ), and congenital anomalies.…”
mentioning
confidence: 99%